Effect of “needle sensation” and the real-time changes in autonomic nervous system activity during acupuncture analgesia - Liu, Zehua; Huang, Jinglei; Yan, Dingshang; Liang, Sha; Zhao, Shatong; Zhang, Mengzhen; Li, Zhongwen; Jiang, Chuliang; Yin, Xiang; Zhang, Yingjun; Hou, Tianshu; Feng, Min (Frontiers in Neuroscience, 2024)
Introduction: Acupuncture analgesia (AA) is widely used in clinical practice. The autonomic nervous system (ANS) may be an important pathway for acupuncture signal transduction. However, real-time changes in autonomic function during AA and the effect of "needle sensation" remain unclear. Methods: We established a human pain model in healthy adults and randomly assigned 128 participants to the model, sham acupuncture, and acupuncture groups in a 1:1:2 ratio. Heart rate variability (HRV), including total power (TP), low-frequency power (LF), high-frequency power (HF), ratio of LF to HF (LF/HF), standard deviation of the normal-normal intervals (SDNN), and root mean square of successive interval differences (RMSSD), were used to assess autonomic function. The visual analog scale (VAS) and efficiency were used to assess the analgesic effect of acupuncture. The Massachusetts General Hospital acupuncture sensation scale (MASS) was used to indicate the intensity of the needle sensation. Anxiety levels were also measured. Finally, the correlation of MASS with HRV, VAS, and anxiety levels was analyzed. Results: VAS decreased after 10 min of needling and 5 min after needle withdrawal in the acupuncture group compared with those in the model group (p=0.038, p=0.020). The efficacy rates were 82.0%, 50.0%, and 61.3% in the acupuncture, model, and sham groups, respectively. These represent significant differences between the acupuncture group and the model and sham acupuncture groups (p<0.001 in each case). No differences were observed between the model and sham acupuncture groups. HF, TP, SDNN, and RMSSD were all increased in the acupuncture group compared with those in the model group (p=0.045, p=0.041, p=0.002, p=0.006, respectively). No differences were observed in the sham acupuncture group compared to the model group (p=0.632, p=0.542, p=0.093, p=0.222, respectively).The LF and LF/HF did not differ among all three groups. A positive correlation was observed between MASS and RMSSD2, LF2, RMSSD4, TP4, VAS5, and anxiety levels. Conclusion: AA was associated with enhanced vagal activity. The intensity of needle sensation was positively correlated with vagal and sympathetic nerve activities. Acupuncture is an effective means of regulating autonomic function, and needle sensation may be an important modulator.